Improving the hydrogen storage performance of lithium borohydride by Ti3C2 MXene. (8th November 2019) - Fan, Yanping; Chen, Dandan; Liu, Xianyun; Fan, Guangxin; Liu, Baozhong
Abstract: Two-dimensional layered material of Ti3 C2 has been used to improve the hydrogen desorption properties of LiBH4 . The results of temperature-programmed dehydrogenation (TPD) and isotherm dehydrogenation (TD) demonstrate that adding the Ti3 C2 contributes to the hydrogen storage performance of LiBH4 . The dehydrogenation temperature decreases and the dehydrogenation rate increases with increasing the adding amounts of Ti3 C2 . The onset dehydrogenation temperature of LiBH4 + 40 wt% Ti3 C2 composite is 120 °C and approximately 5.37 wt% hydrogen is liberated within 1 h at 350 °C. Furthermore, the activation energy of LiBH4 + wt.% Ti3 C2 is also greatly reduced to 70.3 kJ/mol, much lower than that of pure LiBH4 . The remarkable dehydrogenation property of the LiBH4 + 40 wt% Ti3 C2 may be due to the layered active Ti-containing Ti3 C2 and the high surface area of MXene. Highlights: Ti3 C2 MXene significantly improve the dehydrogenation of LiBH4 . Onset dehydrogenation temperature of LiBH4 is reduced to 120 °C. 5.37 wt% hydrogen in 40% Ti3 C2 composite is liberated within 1 h at 350 °C. Improved dehydrogenation is due to layered and high surface area of MXene Ti3 C2 .